2018
DOI: 10.1177/1455072518759829
|View full text |Cite
|
Sign up to set email alerts
|

Is proximity to alcohol outlets associated with alcohol consumption and alcohol-related harm in Denmark?

Abstract: Background: This study examined the associations between distance from residence to the nearest alcohol outlet with alcohol consumption as well as with alcohol-related harm. Methods: Data on alcohol consumption, alcohol-related harm and sociodemographics were obtained from the 2011 Danish Drug and Alcohol Survey (n ¼ 5133) with respondents aged 15-79 years. The information on distances from residence to the nearest alcohol outlets was obtained from Statistics Denmark. Multiple logistic and linear regressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(57 reference statements)
0
3
0
2
Order By: Relevance
“…The exposure to alcohol outlets makes it difficult to resist drinking alcohol even for pregnant woman and under age children. Similarly, a study conducted by Seid et al (2018) found that there is a closer link between close distance of alcohol outlets in places of residence and alcohol use by women. The use of alcohol by pregnant women increases the risk of fetal alcohol spectrum disorder (FASD) in unborn children which is commonly known as the worldwide leading cause of congenital disability (Seid at el, 2018).…”
Section: Proximity To the Residential Areasmentioning
confidence: 83%
See 1 more Smart Citation
“…The exposure to alcohol outlets makes it difficult to resist drinking alcohol even for pregnant woman and under age children. Similarly, a study conducted by Seid et al (2018) found that there is a closer link between close distance of alcohol outlets in places of residence and alcohol use by women. The use of alcohol by pregnant women increases the risk of fetal alcohol spectrum disorder (FASD) in unborn children which is commonly known as the worldwide leading cause of congenital disability (Seid at el, 2018).…”
Section: Proximity To the Residential Areasmentioning
confidence: 83%
“…The study found that the closeness of shebeens is associated with the higher probability of youth consuming alcohol or engaging in binge drinking resulting in more alcohol related problems. In a similar study conducted in Denmark by Seid, Berg-Beckhoff, Stock and Bloomfield (2018) it was hypothesized that proximity of alcohol outlets is associated with a greater alcohol consumption and people engaging in more deviant behaviors such as frequency in drinking patterns. Livingstone at el (2007) asserts that the greater the alcohol availability in societies the more the consumption increases which directly influences alcohol related harm in communities.…”
Section: Discussionmentioning
confidence: 99%
“…Lamb et al [35], in a cross-sectional study sampling 995 women, reported that increasing the number of alcohol outlets within as little as a 3-kilometre radius can be linked to higher levels of the harmful consumption of alcohol among women. Concordantly, Seid et al [34] stated that more reports regarding harmful effects, such as in marriage, relationships, or finance, have been observed in women who live nearer to alcohol outlets.…”
Section: Proximity To Alcohol Outletsmentioning
confidence: 92%
“…Algunos estudios indican que el efecto de la disponibilidad sobre el consumo, y sus consecuencias, varían en función del sexo. Se encontró que la asociación entre disponibilidad y CEEA (Halonen et al, 2013b), o entre disponibilidad y consecuencias negativas (Seid, Berg-Beckhoff, Stock, & Bloomfield, 2018), se expresa entre las mujeres pero no entre los hombres. Estos resultados, y otros que muestran dimorfismos sexuales en los efectos de diferentes factores de riesgo sobre el consumo de alcohol (Foster, Hicks, Iacono, & McGue, 2015;Pilatti, Rivarola Montejano, Lozano, & Pautassi, 2016), ponen de manifiesto la importancia de realizar análisis diferenciados por sexo.…”
unclassified
“…Se encontró una relación positiva y significativa entre la DO y el consumo de alcohol (habitual y CEEA) y la cantidad de consecuencias negativas derivadas de este consumo (Chen, Grube, & Gruenewald, 2010;Connor, Kypri, Bell, & Cousins, 2011;Paschall et al, 2012;Weitzman, Folkman, Folkman, & Wechsler, 2003). En consonancia con algunos (Halonen et al, 2013b;Seid et al, 2018) pero no otros (Brenner et al, 2015;Foster et al, 2017) (Berardo, Fabio, & Pautassi, 2016).…”
unclassified